Analysis of the dependence of the hydraulic system training coefficient in quarry excavators on the concentration of contaminated particles in the working fluid - Abduazizov Nabijon; Nietbaev Arslanbek; Turdiyev Sardor; Zhuraev Akbar; Polvonov Nurbek; Adizov Dostonbek (E3S Web of Conferences)
During the operation of hydraulic excavators, a constant process of contamination of working fluids with atmospheric and other contaminants occurs. Pollutants affecting the system include two main components: mechanical impurities and water. As noted above, for various reasons of an objective and subjective nature, in the work of many researchers during the operation of excavators, changes in the general pollution indicators of working fluids occur, and the uncontrolled state of their contamination leads to a more intensive accumulation of pollution in their tanks in the hydraulic system, failure of their filters. As a result, there is a decrease in the reliability of hydraulic ridges of hydraulic excavators.